PEMANFAATAN ALAT PARAFRASE UNTUK MENINGKATKAN KUALITAS KARYA TULIS MAHASISWA PROGRAM STUDI ILMU PEMERINTAHAN UNIVERSITAS MULAWARMAN - M Aviv Adhitya Putra Pratama; Muhammad Reza Fahlevy; Budiman Budiman (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Plagiarism is a serious issue in academia that affects scientific integrity and the quality of higher education, especially among students who often have difficulty applying proper paraphrasing techniques. To address this issue, the Government Science Study Program of the Faculty of Social and Political Sciences at Mulawarman University conducted a community service activity in the form of a Paraphrasing Tool Utilization Workshop with the aim of improving students' understanding of scientific writing ethics and paraphrasing skills. The implementation method consisted of eight stages, including consultation with the study program coordinator, formation of an organizing committee, coordination with students, preparation of materials, arrangement of the event schedule, creation of digital posters, implementation of the workshop, and final evaluation. The results of the activity showed an increase in student awareness of the importance of academic integrity, with 98.7% of participants stating that their understanding of scientific writing ethics had improved based on the post-workshop questionnaire results. Meanwhile, 97.4% admitted to being more confident in rewriting reading sources in their own language. In addition, 97.3% of participants were able to correctly apply paraphrasing techniques to avoid plagiarism, and an Anti-Plagiarism E-Guide was made available online. This activity is recommended to be carried out continuously with a wider range of participants in order to strengthen academic literacy and build a healthy and ethical academic culture in higher education.